The Effect of Corporate Social Responsibility and Good Corporate Governence on Tax Avoindance : (Mining Companies Listed on Idx in 2018-2020) - Riza Safitri; Putri Zanufa Sari (Journal of World Conference (JWC), 2022)
Abstract This study aims to partially and simultaneously examine and analyze the effect of corporate social responsibility, managerial ownership, independent board of commissioners, audit committee, and institutional ownership on tax avoidance in mining companies listed on the IDX in 2018-2020. This research was conducted on mining companies listed on the Indonesia Stock Exchange in 2018-2020 with purposive sampling technique. The method used in this study uses quantitative methods where the data taken is secondary data. The variables used include the dependent variable, namely tax avoidance, while the independent variables include CSR, managerial ownership, independent board of commissioners, audit committee, and institutional ownership. The results of this study indicate that CSR The significance value is 0.926 and the regression coefficient is -0.028, meaning that there is no significant effect between Corporate Social Responsibility (CSR) on Tax Avoidance. Managerial ownershipthe significance value is 0.722 and the regression coefficient value is -0.052, it means. There is no significant effect between Managerial Ownership on Tax Avoidance.Independent board of commissioners. The significance value is 0.000 and the regression coefficient is +0.647, meaning that there is a significant influence between the Independent Board of Commissioners on Tax Avoidance. Audit Committeethe significance value is 0.572 and the regression coefficient is -0.078, meaning that there is no significant effect between the Audit Committee on Tax Avoidance. Institutional ownershipthe significance value is 0.535 and the regression coefficient is +0.006, meaning that there is a significant effect between institutional ownership and tax avoidance. Simultaneously CSR, managerial ownership, independent board of commissioners, audit committee and institutional ownership valuesignificance of 0.000, meaning that there is a positive influence on Tax Avoidance